Utility of the Ditopic Nature of Magnetically Recyclable NiFe2O4 Nano‐Catalyst for the Green Synthesis of Two Different Spiro[indoline‐pyrrolizine] Scaffolds. Issue 45 (4th December 2018) - Basu, Soumyadip; Kayal, Utpal; Maity, Suvendu; Ghosh, Prasanta; Bhaumik, Asim; Mukhopadhyay, Chhanda
Abstract: Environmentally benign and highly stable magnetic nano powder of NiFe2 O4 was synthesized and characterized by XRD, HRTEM, EDX and Nitrogen BET adsorption isotherm analysis. Also, XPS analysis confirmed the electronic environment as well as the oxidation state of the elements. The NiFe2 O4 catalyst was exploited in one‐pot three‐component synthesis of spiro[indoline‐3, 3′‐pyrrolizine] and spiro[indoline‐3, 5′‐pyrrolo[1, 2‐c]thiazole] scaffolds, because of its ditopic nature which can provide both acidic (Fe 3+ ) and basic (O 2− ) properties, require for the reactions. The desirability of this methodology resides in its simplicity, environmental friendliness, cost effectiveness and easier scaling up for bulk synthesis. Water was utilised as a medium for synthesis of the catalyst as well as the medium of the reaction leading to the product. The synthesized NiFe2 O4 nanocatalyst can be recycled upto six times without any significant loss of activity. Abstract : An efficient recyclable ditopic heterogeneous catalytic behaviour of nano‐sized NiFe2 O4 for the one pot synthesis of spiro[indoline‐3, 3′‐pyrrolizine] and spiro[indoline‐3, 5′‐pyrrolo[1, 2‐c]thiazole] moieties in aqueous medium.